Contrasting Approaches to the Study of Subterranean Life: Biospeleology and Speleobiology - Culver, David C.; Pipan, Tanja (Acta Carsologica, 2023)
The study of subterranean life in general and cave life in particular has been given several names, most especially biospeleology and speleobiology. Historically, biospeleology came first, and signalled that biological study was part of speleology, the science of caves. Speleology itself has come to have several meanings beyond the science of caves, but as a discipline it has not fully developed. Speleobiology emphasizes the connection with biology, especially ecology and evolutionary biology. Biospeleology can be construed as the taxonomic and distributional aspects of the biology of caves while speleobiology can be construed as the aspects pertaining to general biological principles such as evolution.